Population Growth of Tribolium confusum (Coleoptera: Tenebrionidae) on Various Commercial and Non-commercial Flour - Wulandari, Ratna; Astuti, Ludji Pantja; Rahardjo, Bambang Tri (Universitas Panji Sakti, 2025)
Tribolium confusum Jacquelin du Val (Coleoptera: Tenebrionidae) is a major stored product pest that can damage flour in storage. The infestation of T. confusum causes contamination of stored grain, such as flour. Research about the population growth of T. confusum in various commercial and non-commercial flours is still limited. This study aims to determine the population growth of T. confusum in various commercial and non-commercial flours. The study was conducted using the no-choice test method (NCTM). This study used a treatment jar containing 30 g of diet and infested 15 pairs of T. confusum adults for 7 days. Data obtained from this research were analyzed using analysis of variance (ANOVA) and further analyzed using the Duncan Multiple Range Test (DMRT) at a 5% significance level. The results showed that the number of larvae, pupae, and F1 progeny of T. confusum was higher in non-commercial red rice flour (80, 50 individuals; 59, 50 individuals; 57, 50 individuals) compared to other types of flour. The chemical characteristics of diets that can affect the population growth of T. confusum include fat, ash, carbohydrate, and phenol content. In conclusion, understanding the chemical characteristics of flour is crucial for developing a strategy to control T. confusum.